Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1051/0004-6361/201220822
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution of interstellar filaments

Abstract: We investigate the gas velocity dispersions of a sample of filaments recently detected as part of the Herschel Gould Belt Survey in the IC 5146, Aquila, and Polaris interstellar clouds. To measure these velocity dispersions, we use 13 CO, C 18 O, and N 2 H + line observations obtained with the IRAM 30 m telescope. Correlating our velocity dispersion measurements with the filament column densities derived from Herschel data, we show that interstellar filaments can be divided into two regimes: thermally subcriti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
201
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(238 citation statements)
references
References 68 publications
37
201
0
Order By: Relevance
“…Firstly, these internal velocity dispersions are on the order of those measured from observations (Arzoumanian et al 2011) -TI-driven filament formation can reproduce the "turbulent" velocities measured in filaments (e.g. by Arzoumanian et al 2013). Secondly, the fact that different filaments have different central velocities, whilst still being part of a larger bundle of filaments or even projection of interconnected sheets highlights that it is now impossible to conclude from observations of filaments with different central velocities that they are separate filaments -in this work they could equally be part of a TI-formed corrugated sheet, non-uniform in density, temperature and velocity.…”
Section: Filamentsmentioning
confidence: 84%
See 2 more Smart Citations
“…Firstly, these internal velocity dispersions are on the order of those measured from observations (Arzoumanian et al 2011) -TI-driven filament formation can reproduce the "turbulent" velocities measured in filaments (e.g. by Arzoumanian et al 2013). Secondly, the fact that different filaments have different central velocities, whilst still being part of a larger bundle of filaments or even projection of interconnected sheets highlights that it is now impossible to conclude from observations of filaments with different central velocities that they are separate filaments -in this work they could equally be part of a TI-formed corrugated sheet, non-uniform in density, temperature and velocity.…”
Section: Filamentsmentioning
confidence: 84%
“…Line emission observations of C 18 O and N2H + and other molecules towards star forming filaments (Zuckerman & Palmer 1974;Arzoumanian et al 2013;Hacar et al 2013;Furuya, Kitamura & Sinnaga 2014;Henshaw et al 2014;Jiménez-Serra et al 2014;Li et al 2014) have revealed nonthermal line broadening. Arzoumanian et al (2013) presented molecular line measurements of the internal velocity dispersions in 46 Herschel identified filaments.…”
Section: Properties Of Filamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial trans-to supersonic turbulent velocity field as well as the subsequent injection of turbulence by accretion (Klessen & Hennebelle 2010;Arzoumanian et al 2013;Heitsch 2013) are not sufficient to stabilize a filament at a width of 0.1 pc. To overcome this problem, turbulence would have to be replenished in a more efficient way, e.g.…”
Section: Accretion Induced Turbulencementioning
confidence: 99%
“…More recently, the advent of the Herschel satellite has uncovered the filamentary structure in molecular clouds and infrared dark clouds in great detail (e.g. André et al 2010;Könyves et al 2010;Arzoumanian et al 2011Arzoumanian et al , 2013Peretto et al 2012;Schneider et al 2012;Palmeirim et al 2013, but see also the review of André et al 2014).…”
Section: Introductionmentioning
confidence: 99%